Value Orientations of Today’s Youth in the Context of Prosocial Behavior - Алена В. Любцова (Rossijskij psihologičeskij žurnal., 2020)
Introduction. Value orientation of today’s youth is a key problematic aspect of socio-cultural cognition. This paper concentrates on characteristics of value orientations of today’s young people, and how they impact prosocial behavior in this age group. Theoretical Basis. There is a lack of conceptual and systematic understanding of value orientations and their association with young people’s value and meaning sphere. This study represents a first attempt to determine ontogenetic changes in each component of the psychological construct and social development of today’s generation of young people. Results and Discussion. An analytical literary overview provides a background for the main value orientations of youth and their development trends. The fact that traditional values, including family, health, and love still remain main social trends for female youths, represents a gender characteristic of values of young generation. Meanwhile, male youths strive for self-realization. A high level of remuneration remains the main work motivation among young people; they are also interested in the compliance of work with their interests. This paper generalizes and systematizes the results of current studies on age-related characteristics of associations among prosociality and other intrapsychic systems, including volitional regulation, intelligence indicators, and social responsibility. The factors of youth deprivation (egoistic motivation and distortions in the attributive system of trust in the world) influence the age genesis of prosociality. Initiative and intelligence determine prosocial tendencies in adolescence, late adolescence, and early adulthood. The programs for stimulating prosociality should be focused on a mature prosociality. This idea provides conceptual frameworks for objective criteria for the expediency of prosocial forms of behavior, reflexive subjectivity, and personal pleasure from actions for the benefit of another person.